2022
DOI: 10.1038/s41467-022-33173-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of adhesion GPCR GPR110 activation by stalk peptide and G-proteins coupling

Abstract: Adhesion G protein-coupled receptors (aGPCRs) are keys of many physiological events and attractive targets for various diseases. aGPCRs are also known to be capable of self-activation via an autoproteolysis process that removes the inhibitory GAIN domain on the extracellular side of receptor and releases a stalk peptide to bind and activate the transmembrane side of receptor. However, the detailed mechanism of aGPCR activation remains elusive. Here, we report the cryo-electron microscopy structures of GPR110 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…The dissociation (one-and-done) model requires the physical disruption of the NTF/CTF heterodimer [12,[24][25][26], while the nondissociation (tunable) model posits that Stachel-7TM domain engagement occurs through partial allosteric movements of the GAIN domain in intact NTF/CTF aGPCR heterodimers [10,13,17,27,28]. Both scenarios have received support from recent structural studies of active aGPCR 7TM domains [29][30][31][32][33][34][35]. The existence of selfcleavable and non-cleavable aGPCRs underline the feasibility of both models, complicating pharmacological advances.…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation (one-and-done) model requires the physical disruption of the NTF/CTF heterodimer [12,[24][25][26], while the nondissociation (tunable) model posits that Stachel-7TM domain engagement occurs through partial allosteric movements of the GAIN domain in intact NTF/CTF aGPCR heterodimers [10,13,17,27,28]. Both scenarios have received support from recent structural studies of active aGPCR 7TM domains [29][30][31][32][33][34][35]. The existence of selfcleavable and non-cleavable aGPCRs underline the feasibility of both models, complicating pharmacological advances.…”
Section: Introductionmentioning
confidence: 99%
“…Combining structural insights with extensive functional studies, we identify key residues of the orthosteric binding site that are essential for Gα s signalling but dispensable for Gα q signalling. Overall, our work complements other recent aGPCR structures 12 16 and extends them by visualizing ADGRF1 in complex with its most relevant G protein partner in a non-tethered complex, elucidating a functional and structural landscape by which ADGRF1 is activated and uncovering how its structure determines Gα class preference. Furthermore, the mechanistic insights determined here regarding TA engagement to strong and weakly associated G proteins offers valuable insight into how TA mediated activation of aGPCRs may be functionally modulated.…”
Section: Introductionmentioning
confidence: 53%
“…The first structure of an aGPCR 7TM domain was solved for ADGRG3 (GPR97) bound to glucocorticoids in the orthosteric pocket, revealing key residues involved in ligand recognition, conformational switches important for receptor activation, and residues for coupling to G protein 11 . Cryo-EM structures were then reported for seven different aGPCR family members activated by their TAs, including representative GPCR-G protein complexes for all major families of Gα 12 16 . These studies showed that the TA acts an intramolecular ligand for the 7TM domain and identified a canonical binding pose for a conserved hydrophobic interaction motif (TØFØØLM) of the TA in the GPCR orthosteric site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive polar interactions between receptor/Gα s and the deepest insertion of αH5 into the intracellular core of the receptor suggest that GPR174 uses a unique way to bind and engage Gα s , and those observations also indicate that G s is tightly packed against receptor, and this may explain the high level of constitutive activity of GPR174 11,37 and weak ligand-induced G s dissociation activity (see the section "Methods" functional assay). We used the NanoBiT strategy in our complex assembling, the strategy only increases the local concentration of binding partners and cannot force an interaction that does not exist in nature, evidenced by the identical structures of GPR110/G s complexes solved with or without the NanoBiT strategy recently 38,39 . Taken together, our structure of the LysoPS-bound GPR174/G s complex provides a foundation to understand LysoPS signaling and clues for developing LysoPS intervention.…”
Section: Discussionmentioning
confidence: 99%